Histopathological Investigation of Fowl Adenovirus (FAdV) Infections in Broiler Chickens: A Study in Diyala Governorate - Walaa Thaeer; Amer Al-Azzawi (Diyala Journal for Veterinary Sciences, 2025)
Inclusion Body Hepatitis (IBH), is the main serotype caused by Fowl Adenovirus (FAdV), that affecting chickens leading to substantial economic losses in poultry industry worldwide. The virus mostly affects broiler chickens aged 3-6 weeks, resulting in mortality rates ranging from 10-30%. IBH is characterized by friable, enlarged livers with hepatic necrosis and ecchymotic hemorrhages, often accompanied by lesions in the kidney and spleen. This study was performed at the College of Veterinary Medicine, University of Diyala, aim to identifying the strains of this virus and detect the disease to confirm its presence in Diyala Governorate. This was achieved by conducting histopathological examinations on samples collected from post-mortem cases. Twenty-five tissue samples were collected from several organs, including the liver, spleen, and kidney, from five location farms in Baqubah, Al-Khalis, Al-Muqdadiyah, Al-Wajhiyah, and Kanaan. These sections were stained using routine hematoxylin and eosin (H&E) staining protocols. Histopathological examination of tissues infected broiler chickens with IBH- exposed significant pathological changes. Liver sections displayed coagulative necrosis, basophilic intranuclear inclusion bodies within hepatocytes, fatty infiltration, and subacute periportal hepatitis. In the spleen, vascular congestion, hemorrhage, and lymphocyte depletion were detected. Kidney segments exhibited sign of nephritis, tubular degeneration, and mild peritubular mononuclear infiltration. Additionally, the glomeruli displayed mesangial hyperplasia, proliferative glomerulonephritis, and thickening of Bowman’s capsule, while intranuclear inclusion bodies were rarely detected in renal tissues. These findings highlight the extensive tissue damage caused by IBH in affected organs. The results of the current study highlight the pathological effects of FAdV in broiler chickens emphasize the importance of timely detection and characterization of the virus to alleviate its economic effect on poultry rearing in Diyala Governorate